(untitled) (Research, Society and Development, 2021)
The aim of this descriptive study was to verify the relationship between the appearance of oral coinfections resulting from or together with COVID-19 infection in patients. First detected in late 2019 and quickly became one of the global ones, being called SARS-CoV-2, the virus is transmitted from one individual to another by droplets of saliva, the symptoms present themselves as loss of taste, smell, fever, coughing and shortness of breath. New discoveries about the virus arise daily and despite controversies in literature, several changes in oral health and injuries were obtained as oral manifestations of COVID-19, such as dysgeusia, oral ulcers, petechiae, reddened macules, desquamative gingivitis, others. In addition, the disease was also cited as a cause of systemic changes, compromised immune system and predisposing factors to opportunistic coinfections, which may occur as a direct or indirect result of SARS-CoV-2 infection. However, it was found that more studies are needed to guide and clarify possible changes in oral health and the property of cause and effect.